MANAJEMEN PERKEMBANGAN SISWA SD MELALUI PERAN GURU DAN ORANG TUA PADA MASA PANDEMI - Farid Wajdi (Universitas Negeri Malang, 2021)
Abstract: Education as a management tool in shaping the development of the human person plays an important role in dealing with situations and conditions of life. Through education, a person is able to manage, live, face and overcome life's problems. Teachers and parents must play an active role in the learning process. Especially during the Covid-19 pandemic, teachers and parents are expected to be able to provide online learning assistance to students. Good and correct assistance can minimize the occurrence of violence against children, the student's workload is minimal, and it is not too heavy for parents to support their children. This type of research is qualitative through field studies involving teachers and parents of elementary school students. Data collection techniques through observation and interviews. The findings of the study, teachers are not ready and do not understand online learning, especially in using online learning applications, parents do not support the online learning process during the Covid-19 pandemic or new life adaptations. This is due to the economic burden of the family, a lack of understanding of online learning applications, emotions during learning, indifference, and feelings of being overwhelmed by children's assignments given by the teacher. Keywords: Role teacher; parent; pandemic era Abstrak: Pendidikan sebagai sarana manajemen dalam pembentukan perkembangan pribadi manusia berperan penting dalam menghadapi situasi dan kondisi kehidupan. Melalui pendidikan, seseorang mampu mengelola, menjalani, menghadapi, dan mengatasi permasalahan kehidupan. Guru dan orang tua harus berperan aktif dalam proses pembelajaran. Terutama pada masa pandemi covid-19, guru dan orang tua sangat diharapkan dalam melakukan pendampingan pembelajaran online pada siswa. Pendampingan yang baik dan benar dapat meminimalisir terjadinya kekerasan pada anak, kurangnya beban tugas siswa, dan tidak terlalu berat orang tua mendampingi anaknya. Penelitian ini jenis kualitatif melalui studi lapangan yang melibatkan guru dan orang tua siswa SD. Teknik pengumpulan data melalui observasi dan wawancara. Temuan penelitian, guru belum siap dan kurang memahami pembelajaran online terutama dalam menggunakan aplikasi pembelajaran online, orang tua kurang mendukung proses pembelajaran online pada masa pandemi covid-19 maupun adaptasi kehidupan baru. Hal tersebut diakibatkan oleh beban ekonomi keluarga, kurang paham aplikasi pembelajaran online, emosi saat pembelajaran berlangsung, bersikap acuh, dan merasa terbebani dengan tugas anak yang diberikan oleh guru. Kata kunci: Peran guru; orang tua; masa pandemi